Deriving the functional relation of input parameters in single-point incremental forming through dimensional analysis - Oraon, Manish; Sharma, Vinay (Frontiers in Mechanical Engineering, 2022)
The system is design with the basics of fundamental units termed as dimensional analysis (DA). The fundamental units are modeled to figure out some quantitative measures without the knowledge of the system behavior. Subsequently, the dimension analysis-based modeling helps to develop the functional relation of input parameters for the set objectives. The generalized model is validated with the output of experiments with an agreement to adopt the model within a certain range of error. Single Point Incremental Forming (SPIF) is an innovative sheet metal forming technique in which the forming of metal sheets to the desired shape without using dedicated dies. The SPIF investigations and declared results are desperately waiting for its industrial acceptability but yet the optimization of the process is absent. The current study is to develop the functional relation of input parameters of SPIF through dimensional analysis. Five input parameters i.e. Step-down size, area of tool end, feed rate of the tool, the ultimate tensile strength of the work (metal sheet), and density of work (metal sheet) are taken for the modeling for surface roughness of the formed part. The functional relation confirmed that the step-down size (and area of tool end are prominent factors for surface roughness and its influences on output are 150% and 100% respectively. The modified R_a-values are lower than the true and ANN modeled〖 R〗_a and its mean error is noted as 6.136.